Numerical study on the installation effect of a jacked pile in sands on the pile vertical bearing capacities. (May 2022) - Su, Dong; Wu, Zexiong; Lei, Guoping; Zhu, Min
Abstract: The installation effect of a jacked pile in silica sand is investigated numerically. A simplified state-dependent dilatancy model is used to model the sand behavior and the sand grain crushing effect is considered by modifying the critical state line at large confining pressures. The Arbitrary Lagrangian-Eulerian (ALE) technique is adopted to model the pile penetration and the load-displacement behavior at the operational loading stage is simulated using standard finite element method with the initial states being the equilibrium of the pile-jacking-disturbed soil stress and void ratio fields and a free pile head. The numerical procedure has been verified against some calibration chamber tests and centrifuge tests. Simulations of wished-in-place piles are performed for the quantitative study of the installation effect. The results show that the capacity ratios between the jacked and wished-in-place piles become higher for long piles in dense sand. Linear fittings have been applied to obtain the capacity ratios as functions of the relative density and the penetration length-to-diameter ratio, which can be used for a quick estimation of the bearing capacity difference between jacked and wished-in-place piles.